Myopia and glaucoma progression among patients with juvenile onset open angle glaucoma: A retrospective follow up study. (7th April 2021) - Gupta, Shikha; Singh, Abhishek; Mahalingam, Karthikeyan; Selvan, Harathy; Gupta, Prasad; Pandey, Shivam; Somarajan, Bindu I; Gupta, Viney
Abstract: Objective: To identify the risk factors for glaucoma progression, especially the association with myopia, among treated juvenile open angle glaucoma (JOAG) patients. Methods: Glaucomatous progression was analysed in the eyes of JOAG patients with at least 5‐years of follow up in this retrospective study. Baseline variables such as age, inheritance pattern, baseline intraocular pressure (IOP), baseline central corneal thickness, visual acuity, baseline refractive error, spherical equivalent (SE) and duration of follow‐up were noted. Stereoparametric global trend analysis and Moorfields Regression Analysis on confocal scanning laser ophthalmoscopy were used to detect progression. Variables associated with glaucoma progression, with respect to progressors (PG) and non‐progressors (NPG) were analysed. Since both eyes of a patient were taken for analysis, a generalised estimating equation method was used to correct the bias. Results: Among 74 eyes (37 subjects), glaucoma progression was noted in 11 eyes (14.9%) of 8 patients, with a median time to progression of 7.4 years (range 5–15.5 years). For myopes (SE ≤ −1.00 D), glaucoma progression was 18 times more likely than mild and no myopes (>‐1DS) ( p  = 0.03, 95% CI: 1.14, 217.44). The prevalence of myopia in the JOAG, PG and NPG cohorts was 70.3%, 87.5%, and 65.5%, respectively. Myopia progression was noted at follow up in 70% patients. One‐unit increase in baseline vertical cup disc ratio, 1 mmHg increase in IOP fluctuations and 1 dB year −1 depression of visual field were associated with 0.44, 0.06 and 0.07 D year −1 increases in the rate of myopia progression, respectively. Conclusions: JOAG progressors had a greater baseline myopic refraction and a faster myopia development over time. The development of myopia in JOAG eyes could be an indicator of glaucoma progression, and hence progressing myopic (≤−1 D) JOAG patients should be followed up more rigorously.